2017
DOI: 10.1111/acps.12753
|View full text |Cite
|
Sign up to set email alerts
|

Duration of major and minor depressive episodes and associated risk indicators in a psychiatric epidemiological cohort study of the general population

Abstract: As the risk of chronicity was similar for MDD and MinDD, MinDD cannot be dismissed as a merely brief mood state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 30 publications
2
42
0
1
Order By: Relevance
“…Two plausible explanations for this discrepancy are that Hardeveld et al. , basing their findings on the first NEMESIS study, made use of an older CIDI version with less strict criteria for MDD , thereby including recurrent cases at follow‐up more easily, and that as our current cases were more impaired our remitted cases were more healthy at the start. Additional analyses indeed confirm that at baseline, our remitted cases in NEMESIS‐2 scored better on mental functioning ( P = 0.013), less often had a current substance use dependency ( P = 0.002), less often had experienced childhood abuse ( P = 0.000) and less often used general medical care for mental health problems ( P = 0.000) compared to similar defined remitted cases in NEMESIS after adjustment for four sociodemographics assessed in both studies.…”
Section: Discussionmentioning
confidence: 86%
“…Two plausible explanations for this discrepancy are that Hardeveld et al. , basing their findings on the first NEMESIS study, made use of an older CIDI version with less strict criteria for MDD , thereby including recurrent cases at follow‐up more easily, and that as our current cases were more impaired our remitted cases were more healthy at the start. Additional analyses indeed confirm that at baseline, our remitted cases in NEMESIS‐2 scored better on mental functioning ( P = 0.013), less often had a current substance use dependency ( P = 0.002), less often had experienced childhood abuse ( P = 0.000) and less often used general medical care for mental health problems ( P = 0.000) compared to similar defined remitted cases in NEMESIS after adjustment for four sociodemographics assessed in both studies.…”
Section: Discussionmentioning
confidence: 86%
“…A single study, with a long follow-up of 10 months, showed that it is worthwhile to invest in long-term motivation to persist in exercising because of maintenance of the therapeutic effect and prevention of a relapse [47]. The latest results of the Dutch NEMISISstudy show that the median time for a depressive episode was 6 months in MDD and 3 months for a minor depressive episode with a full remission of 75% after 1 year for both [5]. This means that exercise as an adjunctive treatment probably can contribute to remission in the first 6 months, after this period it is probably meaningful to prevent a relapse.…”
Section: Context-related Questionsmentioning
confidence: 99%
“…Depressive symptoms are common in various populations [3]. Recurrence of symptoms of MDD occurs in an unfavourable but fluctuating course in 44% of the patients and a severe chronic course in 12-32% of the patients [4,5]. Pharmacotherapy and psychotherapy, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is characterized by persistent sadness, low mood, and anhedonia, which, like ordinary sadness and grief, are probably forms of “psychic pain” that adaptively focus attention on adverse events that would have reduced fitness, such as loss of a spouse, so as to mitigate the current adversity and avoid future such adversities (Andrews & Thomson Jr, ; Hagen, , ; Horwitz & Wakefield, ; Nesse & Ellsworth, ; Panksepp, ; Syme, Garfield, & Hagen, ; Thornhill & Thornhill, ; Tooby & Cosmides, ; Wakefield, ). In the large majority of cases, MDD symptom levels are proportionate to levels of adversity (Brown & Harris, ; Kendler, Karkowski, & Prescott, ), typically resolve within weeks or months (the median is 6 months; Ten Have et al, ), and the majority of sufferers will experience only a single episode in their lifetimes (Ten Have et al, ), features that are consistent with a functional emotional response to adversity.…”
Section: Aversive But Possibly Adaptive Defensesmentioning
confidence: 99%